(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Title Decision in the Selection of a Private Hospital for Childbirth, the purposes of this research were 1) to examine marketing mix factors influencing the decision in the selection of a Private Hospital for Childbirth, 2) to examine process for Decision in the selection of a Private Hospital for Childbirth, 3) to examine the Relationship between marketing mix factors and process for decision in the selection of a Private Hospital for Childbirth. The study was a quantitative research. The population was women who gave birth from private hospital in 300 cases using a questionnaire. Data was analyzed using Percentage, Mean, T-test, One Way ANOVA, Correlation and Regression Analysis. The results of this study were Most of people are government officers, state enterprise employees who got 20,001-30,000 baht a month answer the questionnaire. First right used in treatment is paying medical treatment fee by self. Influential person to customer is own and a child. Marketing mix factors influencing the decision in the selection of a private hospital for childbirth, treatment and medical care sector overall mean, were at the high significant level, when considered in separate aspects, It was found that had 2 high aspects, good service from medical professions and medical professional abilities, medical treatment fee, overall mean were at the highest level. when considered in separate aspects, It was found that had 2 aspects, medical treatment fee that compared with treatment quality and medical treatment fee that compared with medical service location sector, overall mean, were at the high significant level, when considered in separate 2 aspects is comfortable transportation and hospital near residence, marketing promotion sector overall mean, were at the significant moderate level, when considered in separate aspects, It was found 3 moderate levels, programpackage for special treatment campaign. It can pay by installments for medical treatment fee with only promotional credit card and advertisement on website and social media. Profession sector in overall mean, were at the high important level, when considered in separate aspects, good and suitable behavior, and eagerness in service physical presentation and creation overall mean, were at the high significant level, it was found that had 2 aspects, is comfortable of recreation room and interior and exterior decoration of hospital process. when considered in separate aspects, it was found that had 3 aspects, express service ,express in payment and good service process for decision in the selection of a Private Hospital for Childbirth perception to need overall when considered in separate aspects, It was found most significant with finding information mean when considered in separate aspects is with information from advertisement of hospital and for childbirth alternative assessment overall mean, were at the important moderate level, when considered in separate 2 aspects, significance with expert of medical professions and suggestion from close people influencing decision, decision for service sector. overall mean, were at the important moderate level, when considered in separate aspects, it was found 2 high significant, satisfaction in suggestion from in treatment follow up for suggestion.From results, marketing mix factors influencing the decision in process for service location and treatment and medical service so, the administrators of private hospitals should pay attention in 3 items in service process, should be quicker service process, the customer do not should wait for a much time, location sector, the location of hospital, before opening hospital, should considered about customer group according location of hospital essentially, choose the good place that is suitable transportation, near bus stations, good parking lot and enough garages and treatment and medical service. The hospitals should has workshops for professions in pay attention by service mind and customers to be smiling, kind, polite, and qualify medical profession for well- known professions for hospital standard, for decision process, the administrator of private hospital should focus on alternative assessments make image of the hospitals for being believable, promoting sell, childbirth package campaign, vaccine concurrently for interesting choices for pregnant women who have childbirth. Perception to need, the administrators of the private hospitals choose the communication connecting people and decision for service should has good standard for service according to fee and repayment, make the customers impress.